Implementasi Metode Waterfall dalam Perancangan Sistem Informasi Bank Sampah Seruni Perumahan Pondok Ungu Permai Kota Bekasi (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The Waste Bank is an initiative born out of public concern for the environment, particularly in addressing the growing waste problem. The problem faced by the Seruni Waste Bank Association is that the management of waste deposit data is still carried out using conventional bookkeeping, which often results in errors in recording the nominal amount of waste deposits. This error results in losses for the Waste Bank Association and a lack of transparency between officers and members and customers. The purpose of this study is to help create a waste bank management system so as to reduce losses for the association. The research methodology employed is the waterfall methodology, which involves a research design comprising needs analysis, system design, implementation or coding, program testing and evaluation, and maintenance. The definition of users obtained from the results of observations and interviews resulted in two levels of users: owner and junior. System testing includes blackbox testing with test cases that are all accepted or valid, and user acceptant testing with results that are strongly agreed to be accepted by the association. This system has proven effective in helping officers manage waste bank data, especially in reporting waste deposit transactions, thereby improving the performance and transparency of Seruni waste bank operations.